Robots, AI, and related technologies: A mapping of the new knowledge base - Enrico Santarelli; Jacopo Staccioli; Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
Using the entire population of USPTO patent applications published between 2002 and 2019, and leveraging on both patent classification and semantic analysis, this papers aims to map the current knowledge base centred on robotics and AI technologies. These technologies will be investigated both as a whole and distinguishing core and related innovations, along a 4-level core-periphery architecture. Merging patent applications with the Orbis IP firm-level database will allow us to put forward a threefold analysis based on industry of activity, geographic location, and firm productivity. In a nutshell, results show that: (i) rather than representing a technological revolution, the new knowledge base is strictly linked to the previous technological paradigm; (ii) the new knowledge base is characterised by a considerable - but not impressively widespread - degree of pervasiveness; (iii) robotics and AI are strictly related, converging (particularly among the related technologies) and jointly shaping a new knowledge base that should be considered as a whole, rather than consisting of two separate GPTs; (iv) the U.S. technological leadership turns out to be confirmed.
Keywords: O33; 330; Robotics; Artificial Intelligence; General Purpose Technology; Technological Paradigm; Industry 4.0; Patents full-text